Hubungan Pengetahuan Dengan Sikap Ibu Terhadap Perawatan Lanjutan Bayi Prematur di Rumah Sakit Rs Tk IV. 01.07.03 - Lubis, Tapi Endang Fauziah (Universitas Aufa Royhan, 2019)
Premature babies or preterm babies are babies born alive before 37 weeks' gestation regardless of body weight. Countries with higher preterm birth rates have higher mortality rates. Premature babies 66% die within 4 weeks of birth. The incidence of premature babies in Indonesia is still above the average of other countries, reaching 30% -40%. The purpose of this study was to identify the relationship of knowledge with mothers' attitudes towards the care of premature babies. The design used in this study was analytically with a cross sectional study approach. The number of samples is 30 people. Sampling is done by total sampling. This research was conducted at home for mothers who have premature babies who have been cared for in hospitals. Dr. Pirngadi Medan and has been treated at home. Analyze data with Fisher's exact test. From the results of the study most of the respondents had good knowledge of 20 people (66.7%), and most of the respondents also had a good attitude of 19 19 people (63.3%). It can be concluded that there is a relationship of knowledge with the mother's attitude towards the continued care of premature babies (p value = 0.0001). From the results of this study it is known that the knowledge and attitude of mothers in advanced care of premature babies is good, this is because mothers already understand that premature babies are very susceptible to infection and require intensive care.